Départ o el universo poético-viajero de Gautier - Baynat Monreal, Mª Elena (Anales de Filología Francesa, 2009)
The first trip of Théophile Gautier to Spain really marked his life, his way of thinking and his conception of the world. Testimony of this is his famous Voyage en Espagne, a key reference within the genre of travel literature. Less known are poems related with his trip and published fifteen years later under the title of España. On the first, titled Départ is a poetic reflection on what it means for him and the purpose to travel, what he wanted when he moves, why he came to Spain, as well as important issues the way you see and understand life and the meaning of his existence.